Assuring failure implementation design and policy environment of a federal program provision. - Helms, Lelia B.; Henkin, Alan B.; Kurtt, Sharon B. (1993)
"A viable policy design, considered in policy implementation, should integrate understandings of the increasing autonomy of the public-policy environment, especially where policies are nested within a policy sector. Environmental factors are accentuated in policies employing a strong statute implementation design with little latitude for adaptation and negotiation. A case study of one aspect of the Guaranteed Student Loan Program illustrates the advantage of viewing and designing policies from an ecological perspective in a crowded policy sector"
Keywords: Decision-making - United States; Policy sciences; Public policy - United States